The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1515/aoter-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of refrigerant R407C in multiport minichannel section

Abstract: Analysis of the state of-the-art in research of refrigerant condensation in miniature heat exchangers, so-called multiports, was made. Results of refrigerant R407C condensation in a mini condenser made in the form of two bundles of tubular minichannels from stainless steel with an inside diameter 0.64 mm and length 100 mm have been presented. Two exchangers consisted of four minichannels and 8 minichannels have been investigated. The values of average heat transfer coefficient and frictional pressure drops thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Numerous experimental condensation pressure drop investigations in multiport minichannel condensers were reported by researchers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the past two decades. Most of those investigations were for laminar condensation [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], while a few reported turbulent condensation [4-13, 15-19, 21] friction pressure drop measurements. Cavallini et al [4] reported friction pressure drop gradients for condensation of R236ea, R134a, and R410A in a 1.4 mm diameter multiport minichannel condenser.…”
Section: Multiport Minichannel Condensersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental condensation pressure drop investigations in multiport minichannel condensers were reported by researchers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the past two decades. Most of those investigations were for laminar condensation [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], while a few reported turbulent condensation [4-13, 15-19, 21] friction pressure drop measurements. Cavallini et al [4] reported friction pressure drop gradients for condensation of R236ea, R134a, and R410A in a 1.4 mm diameter multiport minichannel condenser.…”
Section: Multiport Minichannel Condensersmentioning
confidence: 99%
“…Bohdal et al [11] conducted condensation pressure drop experiments in two 0.64 mm diameter multiport minichannel condensers with 4 and 8 parallel channels. The R407C condensation friction pressure gradient data in the range of G ¼ 126-1117 kg/m 2 s and at T sat ¼ 35 C were not validated against widely reported correlations.…”
Section: Multiport Minichannel Condensersmentioning
confidence: 99%
“…where Nu f is a number describing the intensity of the heat transfer as cooling medium flows through a cylindrical horizontal channel. In line with the fact that the range of liquid Reynolds number is in the range from 3000 to 10,000, the Nusselt number was determined by Nu f and was calculated according to the modified Hausen formula [40], the use of which is appropriate in the field of transient and turbulent flow, Re f = 2300 ÷ 15,000. The equation is:…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…The largest discrepancies were found for Kutateładze [44], where MAPE was 91.7%. The above discrepancies result from the fact that the correlations adopted for comparison are recommended for conventional channels [37,40] or flow inside minichannels [42]. Hence, they are of little use for calculating surface condensation in mini spaces.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…The phenomenon of condensation in heat exchangers can occur on a flat surface (in plate condensers), on the external surface of the channels (e.g., in shell and tube condensers) or during the flow of the refrigerant inside the channels (e.g., in air-cooled condensers with external enhancement) [1,9,16]. When refining the problem to the condensation of the refrige-rant in a flow inside channels, one needs to pay attention to the shape of the cross-section [3,6,7] (in the majority of cases, pipe channels with a circular cross-section are used), the hydraulic diameter [5,8,14] and the channel length (i.e.…”
Section: Introductionmentioning
confidence: 99%